Heterotaxy syndrome with agenesis of dorsal pancreas and diabetes mellitus: case report and review of the literature - Cínthia Minatel Riguetto; Samantha Pelichek; Arnaldo Moura Neto (Archives of Endocrinology and Metabolism)
SUMMARY Heterotaxy syndrome (HS) is a rare congenital condition with multifactorial heritance, characterized by an abnormal arrangement of thoraco-abdominal organs and vessels. Patients present with multiple cardiac, gastrointestinal, hepatosplenic, pancreatic, renal, neurological and skeletal disorders without any pathognomonic alteration. Despite the described increased risk of diabetes mellitus (DM) in patients with altered pancreatic anatomy, just one case was reported in Korea regarding the association of HS and DM in a 13-year-old girl. Our report refers to a 40-year-old female Brazilian patient with a history of DM and HS with polysplenia and agenesis of dorsal pancreas without cardiac abnormalities. She presented a worsening glycemic control associated with weight gain and signs of insulin resistance. After a proper clinical management of insulin and oral medications, our patient developed an improvement in glycemic control. Although it is a rare disease, HS with polysplenia and pancreatic disorders can be associated with an increased risk of DM. This case highlights the importance of investigating DM in patients with HS, especially those with pancreatic anatomical disorders, for proper clinical management of this rare condition.